Implementation of Protection for Indonesian Migrant Workers in Malaysia in 2022-2023 - Gustri Eni Putri (UNIDA Gontor, 2025)
Malaysia is the main destination country for Indonesian migrant workers. However, violence and discrimination often befall them. In response to this, Indonesia then issued a policy to protect Indonesian migrant workers in Malaysia in 2022 in the hope that this could be a solution to this problem. This policy was then implemented through a cooperation scheme with Malaysia as a receiving country for Indonesian migrant workers. This research uses the concept Policy Implementation Marilee S. Grindle as a framework for thinking. The result that was obtained was that this policy could not be implemented optimally due to violations committed by Malaysia and the still high rate of violence and discrimination that befell Indonesian migrant workers in Malaysia in 2022-2023.